Pendampingan NIB dan Sertifikasi Halal sebagai Upaya Mendorong Legalitas UMKM di Rewwin, Waru, Sidoarjo - Atina Nabila Ahmad (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2026)
Assistance in obtaining a Business License Number (NIB) and halal certification at Rewwin Housing was carried out as a strategic effort to promote legality and increase the competitiveness of MSMEs. In general, many business actors still do not have legal status due to limited knowledge regarding administrative procedures and digital licensing systems. In fact, business legality is a crucial aspect that can increase consumer trust, expand market access, and strengthen a business's position amidst competition. Sobar et al. (2023), "improving product quality and becoming a service are key factors in increasing the competitiveness of MSMEs," which is supported, among other things, by having a business legality. The mentoring activity was carried out on February 7–8, 2026, using a Participatory Action Research (PAR) approach, which emphasized active participation between the mentor and business actors in identifying obstacles and completing the mentoring process together. Through this process, MSME partners gained practical understanding regarding NIB registration through the OSS system and halal certification applications. The results of the activity showed an increased awareness that business legality is not only an administrative responsibility, but also a strategic increase in business credibility and professionalism. Ridwan et al. (2024) legal assistance can increase the understanding and readiness of MSME actors in developing their businesses sustainably.